Local Polynomial Estimation of Nonparametric Simultaneous Equations Models - SU, Liangjun (Institutional Knowledge at Singapore Management University, 2008)
We define a new procedure for consistent estimation of nonparametric simultaneous equations models under the conditional mean independence restriction of Newey et al. [1999. Nonparametric estimation of triangular simultaneous equation models. Econometrica 67, 565-603]. It is based upon local polynomial regression and marginal integration techniques. We establish the asymptotic distribution of our estimator under weak data dependence conditions. Simulation evidence suggests that our estimator may significantly outperform the estimators of Pinkse [2000. Nonparametric two-step regression estimation when regressors and errors are dependent. Canadian Journal of Statistics 28, 289-300] and Newey and Powell [2003. Instrumental variable estimation of nonparametric models. Econometrica 71, 1565-1578].